THE ROLE OF PSYCHOLOGICAL FACTORS IN SECOND LANGUAGE LEARNING AND TEACHING - Ahmedova Shohsanam Anvarjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Second language learning is a complex and multidimensional process influenced not only by linguistic input and instructional methods, but also by a wide range of psychological factors. In recent decades, research in applied linguistics and educational psychology has increasingly emphasized the importance of learners’ cognitive, affective, and motivational characteristics in determining success in second language acquisition. This article explores the role of psychological factors in second language learning, with a particular focus on motivation, anxiety, self-confidence, and learner autonomy, which are considered essential components in effective language teaching and learning. Motivation is widely recognized as one of the most influential psychological factors in second language learning. Learners who possess strong intrinsic and extrinsic motivation tend to demonstrate higher levels of engagement, persistence, and achievement. Intrinsic motivation, which stems from personal interest and enjoyment, encourages learners to actively participate in language activities, while extrinsic motivation, such as academic requirements or career goals, provides external reinforcement. This study highlights how teachers can foster motivation by creating supportive learning environments, setting clear objectives, and incorporating meaningful and communicative tasks into classroom instruction.